BUSINESS MODEL CANVAS (BMC) ANALYSIS IN JUDES CHICKEN RESTAURANT PALEMBANG - Siti Mega Yulia; Heri Setiawan; Elisa Elisa; Keti Purnamasari (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
Many aspects of daily life, particularly in the professional sphere, have been altered by the worldwide shift toward digital technology. Data Reportal, a research firm, said on its website that as of early 2022, 73.7% of the Indonesian population has access to the internet. When it comes to a company's digital growth, marketing on Instagram is a viable option. The goal of this design is to help grow the market for Palembang's Judes Chicken Restaurant on Jl. Puncak Sekuning by utilizing Instagram and a website built with the help of SWOT (Strength, Weakness, Opportunity, and Threats) and BMC (Business Model Canvas) analysis. Based on the research results, the customer segments of the Judes Chicken Restaurant in Palembang are all genders aged 10 years and over. The value proposition is the unique taste of chili sauce at an affordable price. Customer relationship, namely maintaining the taste of the product and holding promotions every month. Channel, namely implementing promotions on online applications. Revenue streams are cash and credit payments. The key resources owned are the production site, equipment and main materials. Key activities are maintaining the availability of raw materials. Key partnerships are raw material suppliers and plastic packaging suppliers. Cost structure in the form of salary costs, shop rental and raw material costs.